2019
DOI: 10.1007/s12594-019-1321-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry as a Tool for Platinum Group Element (PGE) Exploration – A Case Study from Sittampundi Anorthosite Complex, Southern India

Abstract: The use of surface and ground water for exploration of platinum group elements (PGE) has been studied in the Sittampundi anorthosite complex, Tamil Nadu, south India, where PGE mineralization is known to occur in basic and ultrabasic rocks. Groundwater interacting with mineralized rocks creates a geochemical signature which can be linked to the occurrence and distribution of PGE, especially Pd because of its leachability and relatively high mobility in aqueous environment. Forty surface and ground water sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For example, critical aspects, such as the geological setting, rock types, minerals, pathfinder element enrichments, the drainage patterns, and the geophysical signatures, must favor identifying a deposit. Recent studies indicated that groundwater is an important medium for the geochemical exploration of different styles of mineralization, including those of PGE, gold, and uranium [37][38][39]. Modern commercial miniature devices are commonly lighter than two kilograms and can be used in the field with ease [40].…”
Section: Portable Techniques For Mineral Exploration Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, critical aspects, such as the geological setting, rock types, minerals, pathfinder element enrichments, the drainage patterns, and the geophysical signatures, must favor identifying a deposit. Recent studies indicated that groundwater is an important medium for the geochemical exploration of different styles of mineralization, including those of PGE, gold, and uranium [37][38][39]. Modern commercial miniature devices are commonly lighter than two kilograms and can be used in the field with ease [40].…”
Section: Portable Techniques For Mineral Exploration Studiesmentioning
confidence: 99%
“…In general, the concept is based on the interaction between groundwater and the mineralized zone and the leaching of trace/heavy metals under favorable pH-Eh conditions. The sub-surface recharge of groundwater results in the greater likelihood of rock-water interaction with buried mineralization compared to surface geochemical methods [39]. LED fluorimetry comprises the steps of exciting the uranyl ion in the sample by using electromagnetic energy of suitable wavelengths and measuring the decay with time of the uranium phosphorescence after the termination of the incident electromagnetic radiation.…”
Section: Led Fluorimetermentioning
confidence: 99%
“…Hydrogeochemical prospecting techniques are increasingly being applied in uranium, gold, and PGE exploration studies (Balaram et al, 2019;Giblin & Snelling, 1983;Narayanaswamy, Ramkumar, & Anjaiah, 1998). Geochemical mapping programs are currently being utilized in various socio-economic developmental programmes, including delineation of target zones for enhanced potential through reconnaissance stage investigations (Bhat, Singh, Bhat, Nath, & Guha, 2019).…”
Section: Challenges To Geochemistsmentioning
confidence: 99%
“…Groundwater chemistry is largely a function of mineral composition of the rock formation through which it flows due to water-rock interactions. Water is also used as medium of sampling during mineral exploration studies, because ores and minerals have an effect on the composition of water through dissolution (Balaram et al, 2019;Narayanaswamy et al, 1998). Proper guidelines for the collection of representative water samples are well described in the literature (e.g., Myers, 2006).…”
Section: Precautions During Water Sample Collection Preparation and Storagementioning
confidence: 99%
See 1 more Smart Citation